2011
DOI: 10.1016/j.jjcc.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Change in cardio-ankle vascular index by long-term continuous positive airway pressure therapy for obstructive sleep apnea

Abstract: CAVI was significantly reduced by short-term CPAP and then slightly increased from 1 to 12 months, which was probably due to natural progression associated with the aging process. However, long-term CPAP treatment had the beneficial effect of maintaining CAVI below baseline levels when associated with the use of ACE-I/ARB, the control of blood glucose and the CPAP compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…This suggested that serial assessments of arterial stiffness using CAVI could serve as an indicator of the need for treatment. Moreover, several interventional studies showed that nonpharmacological and pharmacological treatments were associated with an improvement in CAVI [27][28][29] . To determine the utility of CAVI in patients with ACS, more clinical and experimental studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that serial assessments of arterial stiffness using CAVI could serve as an indicator of the need for treatment. Moreover, several interventional studies showed that nonpharmacological and pharmacological treatments were associated with an improvement in CAVI [27][28][29] . To determine the utility of CAVI in patients with ACS, more clinical and experimental studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the benefits of CPAP on reduction of fatal and nonfatal CVD events have been established in multiple large trials [82]. It has also been clearly shown that after CPAP treatment in patients with OSA there was a significant improvement in all indices of AS [79,[83][84][85][86].…”
Section: As In Mets-associated Obstructive Sleep Apnea (Osa)mentioning
confidence: 98%
“…Moreover, the benefits of effective CPAP on reduction of CVD risk and fatal and nonfatal CVD events have been established in multiple large trials [77]. It has also been clearly shown that after CPAP treatment in patients with OSA there was a significant improvement of all indices of AS [74,[78][79][80].…”
Section: As In Mets and Obstructive Sleep Apnea (Osa)mentioning
confidence: 98%